The Effect of Intelligence Games Lesson on Metacognitive Thinking Skills - Epçaçan, Uğur; Bahçeci, Ferhat (Dicle Üniversitesi, 2024)
This study aimed to scrutinize to what extent the intelligence games course affects the metacognitive thinking skills of seventh-grade secondary school students. The research consists of a mixed method in which the quasi-experimental model from quantitative methods and the case study design from qualitative methods are used. The study group consisted of 40 participants from seventh-grade students in a secondary school in the 2021-2022 academic year. 20 of the participating students were in the experimental group and they chose elective intelligence games lesson, and the remaining 20 students were in the control group and they did not choose the elective intelligence games lesson. For quantitative data analysis, non-parametric tests, the Wilcoxon signed-rank test for related measurements, and the Mann Whitney U-test for unrelated measurements were used. Descriptive analysis was used for qualitative data. Research results revealed that the intelligence games lesson significantly affected metacognitive thinking skills. The views stated by the students after the intervention also supported this finding. Hence, it can be suggested that the intelligence games lesson, should be applied at other education levels and the necessary workshop environments should be provided.

Bu araştırmada zekâ oyunları dersinin ortaokul yedinci sınıf öğrencilerinin üst bilişsel becerilerine etkisinin incelenmesi amaçlanmıştır. Araştırma, nicel yöntemlerden yarı deneysel model ile nitel yöntemlerden durum çalışması deseninin kullanıldığı karma bir yöntemden oluşmaktadır. Çalışma grubunu 2021-2022 eğitim-öğretim yılında bir ortaokul yedinci sınıf öğrencilerinden 40 katılımcı oluşturmuştur. Katılımcı öğrencilerden 20'si deney grubunda olup seçmeli zekâ oyunları dersini seçmiş, geri kalan 20 öğrenci ise kontrol grubunda olup seçmeli zekâ oyunları dersini seçmemiştir. Nicel verilerin analizinde parametrik olmayan testlerden, Wilcoxon işaretli sıralar testi ile Mann Whitney U-testi kullanılmıştır. Nitel verilerde ise betimsel analiz tekniğine başvurulmuştur. Araştırma sonuçları, zekâ oyunları dersinin, üst bilişsel düşünme becerilerini anlamlı düzeyde etkilediği ortaya koymuştur. Uygulama eğitiminden sonra görüşlerine başvurulan öğrencilerin bu durumla ilgili ortaya koyduğu fikirler de bunu destekler niteliktedir. Bu nedenle, zekâ oyunları dersinin, eğitimin diğer kademelerinde de uygulanması ve bunun için gerekli atölye ortamlarının oluşturulması önerilebilir.
Zekâ Oyunları Dersinin Üst Bilişsel Düşünme Becerilerine Etkisi
Keywords: Curriculum Development in Education; Eğitimde Program Geliştirme